What the Bible is all about for young explorers : based on the best-selling classic by Henrietta Mears - Blankenbaker, Frances (Regal Books, 1986)
A discussion of the origin, significance, and contents of the Bible, with a book-by-book analysis of events and timelines, photographs, and maps to pinpoint when and where they happened.